Application of Atangana–Baleanu fractional derivative to MHD channel flow of CMC-based-CNT's nanofluid through a porous medium. (November 2018) - Saqib, Muhammad; Khan, Ilyas; Shafie, Sharidan
Highlights: ABC derivatives has been applied to convective flow within microchannel media. CMC based carbon nanotubes CNT's MHD nanofluid is studied. Both time Markovian and Non-Markovian properties of ABC derivatives have been used. The Zakian's, Sehfest's and Tzou's numerical approaches have been utilized. Results have been displayed and studied graphically. Abstract: The objective of this article is to apply the Atangana–Baleanu derivative fractional in Caputo sense to convective flow of Carboxy–Methyl–Cellulose (CMC) based Carbon nanotubes (CNT's) nanofluid in a vertical microchannel. The magnetohydrodynamic (MHD) flow through a porous medium together with heat transfer is considered. The Atangana–Baleanu fractional derivative without singular and the non-local kernel is used in the mathematical formulation to get the time fractional governing equations subject to physical initial and boundary conditions. The Laplace transform technique is used to obtain the exact analytical solutions for velocity and temperature distributions. Finally, the influence of parameters of interest is studied through plots and discussed physically.